Policeman Bluejay - Baum, L. Frank (Saga Egmont, 2021)
Originally released under the pseudonym Laura Bancroft, ‘Policeman Bluejay’ is a children’s story by the famous ‘Oz’ author L. Frank Baum. Friends Twinkle and Chubbins are lost in the Great Forest when they are placed under a spell by the evil Tuxix which turns them into small birds. As birds, the children meet Policeman Bluejay, who teaches them about the ways of the animals of the forest and the suffering the animals endure at the hands of humans. Twinkle and Chubbins will encounter many dangers themselves before they can hope to be returned to their human forms. A delightful tale all about the importance of respecting the living things around us.